Political godmother : Nackey Scripps Loeb and the newspaper that shook the Republican Party - Heckman, Meg (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"A biography of Nackey Scripps Loeb, the longtime publisher of the "Manchester (NH) Union Leader," that traces connections between her influence and our current political moment"--